2020
DOI: 10.1007/s13304-020-00910-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic segmental resection for tumours of the Angle of Treitz: a challenging but feasible surgical option. Results from a retrospective case-series analysis

Abstract: Tumours of the small intestine are rare and account for about 5% of gastrointestinal tract neoplasms. The angle of Treitz (AT) could be defined as the intestinal loop comprised between the third duodenal portion and the first 10 cm of jejunum. A gold standard surgical treatment for AT neoplasm has not yet been well defined. This paper is focused on a very rare disease and at the best of our knowledge this is the largest case series in the literature about the Laparoscopic Segmental Resection (LSR) of AT tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Especially, the superior mesenteric artery, superior mesenteric vein, and the confluence of the inferior mesenteric and splenic veins are close by, and the duodenojejunal junction is firmly adherent to the retroperitoneum. Therefore, there is a risk of injuring these major vessels and the intestine during mobilization around the ligament of Treitz [7,18]. In the present case, an intracorporeal delta-shaped anastomosis was performed.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Especially, the superior mesenteric artery, superior mesenteric vein, and the confluence of the inferior mesenteric and splenic veins are close by, and the duodenojejunal junction is firmly adherent to the retroperitoneum. Therefore, there is a risk of injuring these major vessels and the intestine during mobilization around the ligament of Treitz [7,18]. In the present case, an intracorporeal delta-shaped anastomosis was performed.…”
Section: Discussionmentioning
confidence: 80%
“…Contrarily, there have been some reports of totally laparoscopic surgery for tumors of the angle of Treitz [7,18]. Tanaka et al and Bracale et al have reported a case of a GIST at the angle of Treitz that was treated with totally laparoscopic resection, followed by an intracorporeal duodenojejunostomy between the second or third duodenal portion and the jejunum [7,18]. They considered this procedure as technically demanding due to the anatomical complexity around the ligament of Treitz [7].…”
Section: Discussionmentioning
confidence: 99%
“…This non-specific nature of the symptoms makes that the diagnosis is often late, moreover, in our second patient the tumor was palpable at the time of diagnosis. The localization at the angle of Treitz presents another diagnosis problem, which is the inaccessibility of the area by methods conventional endoscopy makes the diagnosis difficult [3,8,9]. barium meal radiography of the digestive tract is useful for detecting endoluminal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Barium meal radiography of the digestive tract is useful for detecting endoluminal diseases [4], CT enteroclysis using spiral and multidetector-row CT with an enteral contrast agent has become the radiographic diagnostic tool of choice for suspected small bowel neoplasms because the sensitivity and specificity are 100% and 95%, respectively. gives useful information regarding the location and the anatomical relationships between the mass and the surrounding structures, including vascular infiltration and invasion of adjacent organs [4,9]. However, Biopsy is accepted as gold standard for diagnosing gastrointestinal tumours and it could be useful to properly plan a surgical approach with radical intent [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation